Upaya Peningkatan Derajat Kesehatan Anak-Anak di Community Learning Center Kinabalu, Malaysia melalui Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) - Endang Sri Wahjuni; Nur Shanti Retno Pembayun; Febrita Ardianingsih; Nur Ilahi Anjani; Hafshah Yasmina Abidah; Nastiti Aryudaningrum; Evy Wulandari; Susi Susanti; Tita Rachma Ayuningtyas; Anja Hesnia Kholis; Nurullia Hanum Hilfida; Resinta Rahma Mareta Saputri; Natali Anno Angel Simamora (JURPIKAT, 2026)
This community service program focuses on improving clean and healthy living behavior (PHBS) among children at the Community Learning Center (CLC) Kampung Melayu Sulaiman, Sandakan, Sabah, Malaysia, a migrant community with limited access to health education. The program aims to enhance students’ knowledge and practices related to PHBS through structured and participatory educational activities. A Participatory Action Research (PAR) approach was employed, involving students, teachers, and CLC administrators in the processes of needs identification, planning, implementation, evaluation, and follow-up. Activities were carried out both online and onsite through health education sessions, handwashing and toothbrushing demonstrations, and the distribution of educational materials. The results indicate an improvement in students’ knowledge, basic PHBS skills, and behavioral changes such as washing hands before meals and maintaining personal hygiene. Overall, the program positively contributed to increasing children’s health awareness and strengthening teachers’ capacity to continue PHBS education independently